الأحكام الفقهية المتعلقة بموت الدماغ "دراسة فقهية مقارنة - صوالح عمار, نجاح (University of eloued جامعة الوادي, 2015)
The research tries the subject of the fact brain death, from where considered real death for human and shall be subject to all the provisions of death considered religiously, where doctors believed that the brain damage and has ceased to perform its functions fully irreversible halt is surely a final, even if some of the functions of the body are powered by resuscitation equipment, this stage is the best of times for the transfer of members from this dead human brain to those who need it, and here it was necessary to stand up to this calamity and knowledge of Islamic law where scientists stand, based on the above, the search is divise ontwo chapters where we study In the first chapter the medical truth and legitimacy of the death of the brain, while the second chapter we dealt with the provisions of the brain death, in conclusion the research find some results and recommendations
شريعة وقانون
Keywords: الأحكام الفقهية /موت الدماغ/الأحكام; Fiqh rulings / brain death / rulings